You are on page 1of 8

# n an bn pn f(an) f(bn) f(pn) er f(x)=x-2^(-x)

## 0 0 1 0.5 -1 0.5 -0.20711 a1=0

1 0.5 1 0.75 -0.20711 0.5 0.155396 0.333333 b1=1
2 0.5 0.75 0.625 -0.20711 0.155396 -0.02342 0.2
3 0.625 0.75 0.6875 -0.02342 0.155396 0.066571 0.090909
f(x)=x-2^(-x)
n pn f(pn) g(pn) er f(x)=x^4-2x^2+x-2
0 1 -2 1.316074 p0=1
1 1.316074 -1.14803 1.42712 0.240164
2 1.42712 -0.49819 1.468165 0.077811 g(x)=(2x^2-x+2)^(1/4)
n pn f(pn) f'(pn) er f(x)=x^4-2x^2+x-2
0 2 8 25 f'(x)=4x^3-4x+1
1 1.68 2.001142 13.24653 0.190476 p0=2
2 1.528931 0.318184 9.180572 0.098807
n p(n-1) p(n) p(n+1) f(p(n-1)) f(p(n)) f(p(n+1)) er f(x)=x^4-2x^2+x-2
0 2 3 1.857143 8 64 4.854644 p(-1)=2
1 3 1.857143 1.763337 64 4.854644 3.21273 0.053198 p(0)=3
2 1.857143 1.763337 1.579788 4.854644 3.21273 0.816997 0.116186
f(x)=x^4-2x^2+x-2
n xl xu xr f(xl) f(xu) f(xr) er f(x)=x^4-2x^2+x-2
0 1 2 1.2 -2 8 -1.6064 xl=1
1 1.2 2 1.333777 -1.6064 8 -1.05944 0.1003 xu=2
2 1.333777 2 1.411688 -1.05944 8 -0.60254 0.055189
f(x)=x^4-2x^2+x-2